IgE-Selective Immunoadsorption for Severe Atopic Dermatitis - Kasperkiewicz, Michael; Mook, Sophie-Charlotte; Knuth-Rehr, Diana; Vorobyev, Artem; Ludwig, Ralf J.; Zillikens, Detlef; Muck, Philip; Schmidt, Enno (Frontiers in Medicine, 2018)
Introduction: Recent reports proposed the application of immunoadsorption for patients with recalcitrant atopic dermatitis and high serum IgE levels. However, experience with this novel treatment approach, especially with the newly available IgE-specific adsorber, is limited and recommendation for its use in clinical practice awaits evidence from more studies. Materials and methods: Patients with severe atopic dermatitis (SCORAD ≥ 60) and total serum IgE levels ≥ 750 kU/L were included in this study. The treatment protocol consisted of 2 cycles of 5 consecutive treatments with IgE-selective immunoadsorption 3 weeks apart. Results: Ten patients were enrolled and 4 patients completed the study. The mean SCORAD was significantly improved by up to 43% within a few weeks and until the end of a 6-month follow-up period, with 50% of patients achieving an at least 50% individual reduction of the baseline SCORAD. Each immunoadsorption cycle induced a temporal average decrement of total serum levels of IgE, IgM, IgA, and IgG by 92%, 43%, 38%, and 35%, respectively. Except for one case of Staphylococcus aureus septicaemia, no major adverse events occurred. Conclusion: Although limited by a considerable withdrawal rate, our observations strengthen our and other recent results further suggesting that IgE-selective IA is an effective treatment option for patients severely affected by atopic dermatitis with highly elevated IgE levels.